Dream and reality: experience of philosophical meditations - Гончаренко, К. С. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
Introduction. The article is aimed at revealing the value of the dream problem from the philosophical perspective by proving that the phenomenon of dream is not the subject of study of psychoanalysis or literature exclusively; at defining the philosophical concepts of the dream. The vast majority of research materials of dream belong to the fields of medicine, psychoanalysis, neurophysiology, as well as the arts and literature. Philosophical attempts to comprehend the problem of dream are predominantly based on the grounds of the real and the imaginary. The aim and tasks of the work are to present the meaning of the problem of dream in the light of philosophy, the specifics of philosophical discussions about it; to identify approaches in philosophy that make it possible to understand the phenomenon of dream. Research methods. The methodological basis of the work is the approaches of some contemporary Ukrainian philosophers who deal with the problems of the method. In particular, the study involved the heritage of Mozgova N.G., Drotyanko L.G. Discussion. In research, dream acts as a mental failure, this helps a person to avoid, at least for a while, traumatic reality. Due to the absurd, it is possible to deny deliberately false theories, things, states that can dispel the illusion of importance, involvement, authenticity. Dream is a popular topic in arts because it is a fertile ground for fantasy expression. Dream is often a matter for discussion and interpretation. These discussions, in the vast majority of cases, represent certain characteristics of dream (but not immersion in the subject itself). Pictures, collages are devoid to the usual way of perceiving the image, as if forcing the viewer to wake up and escape from the state of sleep. Research results. It is undeniable that most concepts that seek to explain or at least describe sleep and dreams are psychoanalytic reflections. Dreams, as a special language of social, are rethought by E. Fromm, A. Adler and others. J. Lacan departs from classical Freudian theory and blurs the boundaries between dream and imagination, and accordingly places the dream on a level with reality. The dream is expressed through the creative ability of man. K. Horney, who views the neurotic personality, on the contrary, augments reality and views dream as a distraction that beautifies reality. In her research, dream lets avoid traumatic experience. Conclusion. Dream is a subjective state that is revealed only to those who are immersed in it. Over and above, we come to the conclusion that the categorical apparatus of any of the industries trying to explain sleep is too limited. And that is why all we have are descriptive models of this phenomenon, or an attempt to reproduce it. Which, in turn, only confirms the idea that the dream needs a deep philosophical reflection?